Handball match analysis: Computerized notation system - Skarbalius, A.; Krusinskiene, R. (International Journal of Computer Science in Sport, 2002)
Competition analysis provide information about past sport performances and serves for predictive model development (Franks & McGarry 1996). Performance structure in handball is of specifically complex character. One of the main solutions of these inherent problems has been the use of notational computerized analysis systems, which allows generate and edit match analysis reports directly after the match. Presently information on handball is most frequently provided applying the WIGE MIC electronic version. Though this analysis of matches is very wide and informative, it still lacks other extremely important factors characterizing the performance of the team: